2019
DOI: 10.3177/jnsv.65.19
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Immature <i>Citrus tumida</i> Hort. ex Tanaka Peels Suppressed Body Weight Gain and Fat Accumulation in a Mouse Model of Acute Obesity

Abstract: Citrus fruits have several potential benefits for maintaining our health. In this study, we investigated the anti-obesity effects of immature Citrus tumida hort. ex Tanaka (C. tumida) peels using an acute obesity mice model. C57BL/6J male mice were divided into 2 groups; HFD-LL subjected to a high fat diet (HFD) and constant light exposure (LL), and HFDC-LL subjected to a HFD containing immature peel powder of C. tumida (5% w/w) and LL. Dietary ingestion of immature C. tumida peels significantly suppressed bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Dietary ingestion of Citrus tumida Hort. ex Tanaka peels powder (5% w/w) suppressed BW gain by decreasing epidydimal, perirenal, and subcutaneous fat weights (Sato et al, 2019).…”
Section: Antibacterial Potentialmentioning
confidence: 99%
“…Dietary ingestion of Citrus tumida Hort. ex Tanaka peels powder (5% w/w) suppressed BW gain by decreasing epidydimal, perirenal, and subcutaneous fat weights (Sato et al, 2019).…”
Section: Antibacterial Potentialmentioning
confidence: 99%
“…After this design, 31 articles remained, the full texts of which were analyzed, thus yielding 27 articles that were finally included in the qualitative synthesis ( Figure 1 ; Tables 1–3 ). Of these, 22 studies were preclinical trials ( Vinson et al, 1998 ; Bok et al, 1999 ; Terpstra et al, 2002 ; Zulkhairi et al, 2010 ; Ding et al, 2012 ; Kang et al, 2012 ; Raasmaja et al, 2013 ; Lu et al, 2013 ; Kim et al, 2013 ; Muhtadi et al, 2015 ; Dinesh and Hegde, 2016 ; Shin et al, 2016 ; Ashraf et al, 2017 ; Fayek et al, 2017 ; Chou et al, 2018 ; Feksa et al, 2018 ; Mir et al, 2019 ; Sato et al, 2019 ; Hase-Tamaru et al, 2019 ; Ling et al, 2020 ; Ke et al, 2020 ; Lee et al, 2020 ), 3 were exclusively clinical studies ( Gorinstein et al, 2007 ; Toth et al, 2015 ; Cai et al, 2017 ) and 1 study contained preclinical and clinical protocols ( Mollace et al, 2011 ) ( Figure 1 ). For the quantitative synthesis, 25 articles ( Vinson et al, 1998 ; Bok et al, 1999 ; Gorinstein et al, 2007 ; Zulkhairi et al, 2010 ; Mollace et al, 2011 ; Ding et al, 2012 ; Kang et al, 2012 ; Terpstra et al, 2012; Kim et al, 2013 ; Lu et al, 2013 ; Raasmaja et al, 2013 ; Muhtadi et al, 2015 ; Dinesh and Hegde, 2016 ; Shin et al, 2016 ; Ashraf et al, 2017 ; Cai et al, 2017 ; Fayek et al, 2017 ; Chou et al, 2018 ; Feksa et al, 2018 ; Hase-Tamaru et al, 2019 ; Mir et al, 2019 ; Sato et al, 2019 ; Ke et al, 2020 ; Lee et al, 2020 ; …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 22 studies were preclinical trials ( Vinson et al, 1998 ; Bok et al, 1999 ; Terpstra et al, 2002 ; Zulkhairi et al, 2010 ; Ding et al, 2012 ; Kang et al, 2012 ; Raasmaja et al, 2013 ; Lu et al, 2013 ; Kim et al, 2013 ; Muhtadi et al, 2015 ; Dinesh and Hegde, 2016 ; Shin et al, 2016 ; Ashraf et al, 2017 ; Fayek et al, 2017 ; Chou et al, 2018 ; Feksa et al, 2018 ; Mir et al, 2019 ; Sato et al, 2019 ; Hase-Tamaru et al, 2019 ; Ling et al, 2020 ; Ke et al, 2020 ; Lee et al, 2020 ), 3 were exclusively clinical studies ( Gorinstein et al, 2007 ; Toth et al, 2015 ; Cai et al, 2017 ) and 1 study contained preclinical and clinical protocols ( Mollace et al, 2011 ) ( Figure 1 ). For the quantitative synthesis, 25 articles ( Vinson et al, 1998 ; Bok et al, 1999 ; Gorinstein et al, 2007 ; Zulkhairi et al, 2010 ; Mollace et al, 2011 ; Ding et al, 2012 ; Kang et al, 2012 ; Terpstra et al, 2012; Kim et al, 2013 ; Lu et al, 2013 ; Raasmaja et al, 2013 ; Muhtadi et al, 2015 ; Dinesh and Hegde, 2016 ; Shin et al, 2016 ; Ashraf et al, 2017 ; Cai et al, 2017 ; Fayek et al, 2017 ; Chou et al, 2018 ; Feksa et al, 2018 ; Hase-Tamaru et al, 2019 ; Mir et al, 2019 ; Sato et al, 2019 ; Ke et al, 2020 ; Lee et al, 2020 ; Ling et al, 2020 ) were selected. The level of agreement among the reviewers was 0.470, being considered as moderate.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that citrus concentrate of CK has a potential to inhibit the lipid accumulation. In Sato's research, immature citrus fruit power intake showed the antiobesity effect by decreasing blood lipids (Sato, Goto, Inoue, Miyaguchi, & Toyoda, ).…”
Section: Resultsmentioning
confidence: 99%